The Impact of Body Composition on Wound Healing in Type 2 Diabetes Patients: A Systematic Review - Sulfikar, Andi; Mulyati, Mulyati; Hasni, Hasni; Taher, Rusli; Lukman, Sartika; Muhammadong, Muhammadong; Tobang, Rindani Claurita; Restika BN, Indah (Journal of Health and Nutrition Research, 2025)
Wound healing in patients with type 2 diabetes mellitus (T2DM) presents a major clinical challenge, particularly due to alterations in body composition such as reduced muscle mass and increased fat mass. This systematic review aimed to synthesize current evidence regarding the impact of body composition on wound healing effectiveness in T2DM patients. Literature was retrieved from PubMed, ProQuest, Wiley Online Library, and Google Scholar, targeting observational and experimental studies published between 2015 and 2025. Keywords included "type 2 diabetes mellitus", "wound healing", "body composition", "sarcopenia", and "obesity". Articles were selected based on predefined inclusion and exclusion criteria. Methodological quality was assessed using the Critical Appraisal Skills Programme (CASP) checklist. A total of seven eligible studies were included and analyzed narratively. The findings from the 4 articles analyzed showed that low muscle mass (sarcopenia) and high fat mass (obesity) were associated with delayed wound healing in T2DM patients. Some studies indicate that patients with better body composition balance, such as higher muscle mass index, experience faster wound healing. Heterogeneity in measurement methods and study populations limits the strength of these conclusions. This review supports the hypothesis that body composition significantly influences wound healing outcomes in T2DM. Muscle mass reduction may impair tissue repair by limiting perfusion and immune responses, while increased fat mass may contribute to chronic inflammation that hinders tissue regeneration. Further longitudinal research with standardized assessments is needed. Interventions that promote muscle mass gain and fat mass control may be essential components in wound management strategies for diabetic patients.